Restrictions on data-driven political micro-targeting in Germany - Simon Kruschinski; André Haller (Internet Policy Review, 2017)
The revitalisation of canvassing in recent elections is strongly related to campaigns growing possibilities for analysing voter data to gain knowledge about their constituents, identifying their most likely voters and serving up personalised messages through individual conversations. The research literature about political micro-targeting hardly ever focusses on campaigns in parliamentary democracies with strict data protection laws. Based on in-depth expert interviews we introduce a framework of constraints in strategic political communication and reveal several restrictions on the macro, meso and micro levels which hinder the implementation of sophisticated data strategies in Germany. We argue that political micro-targeting highly depends on system-level contextual factors, budgetary and legal restraints, party structures and even individual decisions and knowledge on behalf of the campaign leadership.
Keywords: 300; Micro-targeting; Canvassing; Campaigning; Politics; Qualitative data